Management of Recurrent Tube Exposure in A Challenging Scenario - Meena Menon; Aditi Singh; Anand Balasubramaniyam (Delhi Journal of Ophthalmology)
Glaucoma drainage devices (GDD) remain an effective option for management of refractory glaucoma. However, GDD surgery is not without its complications, including conjunctival erosion and patch graft thinning, to name a few, leading to tube exposure eventually. In our case the patient had various ocular risk factors for tube exposure, thus we used multiple treatment options to prevent recurrent exposure and subsequent complications. A 42 year old lady presented with complaint of sudden decrease in right eye vision, following blunt trauma. On examination, she was found to have retinal detachment in the right eye. She underwent retinal detachment surgery with 360o scleral buckling. She developed intractable glaucoma following surgery, for which Ahmed Glaucoma Valve was implanted after scleral buckle removal. She had two instances of tube exposure. The first was managed with direct conjuctival closure. For the second, a scleral patch graft was used, which was covered with conjunctiva from the inferior fornix and amniotic membrane secured over it. She was on a course of tablet doxycycline 100mg / day, for 2 months. One and a half years after surgery there are no further incidents of tube exposure with well controlled intraocular pressure. Erosion of the drainage tube after shunt surgery is a potentially serious problem. While many techniques and materials are successfully used to address this situation, further studies are required to determine the best repair method.